Microsoft teams y su influencia en el proceso de aprendizaje de las matemáticas, Unidad Educativa Aguirre Abad, Montalvo, 2022 - Filian Cordova, Holger (2022)
At an international level, the teaching-learning process has developed different ways to strengthen the metacognition of students, where the use of technology plays an important role, in the context of online teaching through various software that allows the pedagogical process to be developed with the use of virtual environments, where the most useful for secondary education is Microsoft Termas. In Latin American countries, there are various technological tools that allow the teaching process in a motivating way, with recreational activities in virtual environments such as Moodle, Classroom and Microsoft Teams. In Ecuador, the Education System in the 2020-2021 school year decided to use the Microsoft Teams software. The first chapter presents the contextualization of the problem at the international, regional and national level, under the deductive method in order to present a basis that precedes the problem posed, in addition to the justification, objectives, hypotheses, of the problem under study. In the second chapter, the foundation of the theoretical framework is evident, distributed in the background of the proposed variables, in a deductive way, then the theoretical base that responds to the operationalization of the variables, followed by the conceptualization of the main variables and the dimensions to which just like the indicators. The third chapter presents the methodology used throughout this research work. First, the type of research, methodological design, research approach, unit of analysis, techniques and measurement instrument applied to a specific field or sample are presented. by the researcher. Finally, the results of the frequencies observed in the items are presented, followed by the statistical method applied in descriptive statistics and inferential statistics. Which allows determining the discussions, conclusions and recommendations.